English pronunciation in use : Intermediate (Self-study and classroom use) - Hancock, Mark (UK Cambridge University Press, 2012)
Fifty easy-to-use units cover all aspects of pronunciation, including individual sounds, word stress, connected speech and intonation. An additional reference section offers a glossary of specialized terms, help with the pronunciation of numbers and geographical names and fun exercises on phonemic symbols and minimal pairs.
Keywords: Ngôn ngữ Anh